A Study Of Brand Loyalty In The Fast Food Industry In Malaysia - Kam Tai, Cindy Cheah (2009)
This study aims to provide insight on the fast food brand loyalty, which shed light into the establishment of a successful fast food restaurant in Malaysia by taking into considerations the understanding in the areas of customer satisfaction in the fast food restaurants, the possible loyalty behavioural intentions and further delve into the important elements of brand loyalty.